Ascomycetes versus Spent Mushroom Substrate in Mycoremediation of Dredged Sediments Contaminated by Total Petroleum Hydrocarbons: The Involvement of the Bacterial Metabolism - Simone Becarelli (MDPI AG, 2021)
Two mycoremediation approaches for the depletion of the total petroleum hydrocarbons in dredged sediments were compared: co-composting with spent mushroom substrate (SMS) from Pleurotus ostreatus and bioaugmentation with Lambertella sp. MUT 5852, an ascomycetes autochthonous to the sediment, capable of utilizing diesel oil its sole carbon source. After 28 days of incubation, 99% depletion was observed in presence of Lambertella sp. MUT 5852. No total petroleum hydrocarbon depletion was observed in sediment co-composting with the SMS after 60 days of incubation. 16S rDNA metabarcoding of the bacterial community was performed to evaluate the potential synergism between fungi and bacteria in the bioremediation process. The functional metagenomic prediction approach indicated that the biodiversity of the bacterial genera potentially involved in the degradation of TPH was higher in sediment bioaugmented with Lambertella sp. MUT 5852, which resulted in being mandatory for TPH depletion. Mechanisms of co-substrate inhibition of the hydrocarburoclastic bacterial species, due to the bioavailable organic matter of the SMS, are suggested to be involved in the observed kinetics of TPH depletion, failing in the case of SMS and successful in the case of Lambertella sp. MUT 5852.